THE EFFECT OF FACILITIES AND SERVICES RATES ON THE PATIENT VISITS AT JUNAIDI DOCTOR’S CLINIC KAMPA DISTRICT - Mughnii Yunihati; Zamhir Basem; Adi Setiawan (Jurnal Riset Manajemen Indonesia, 2020)
Research to determine the effect of facilities and services rates on the patient visits at Junaidi Doctor’s Clinic Kampa District. Types and sources of data used in this study are primary data and secondary data, while data collection techniques used in this study were questionnaires, file research, observation and interviews. The population in this research were all patients who used health and general control services at the Junaidi Clinic, Kampa District which in 2019 totaled 2.645 patients and based on the Slovin formula, it is known that the number of samples in this research was 100 patients who used health and general control services at the Junaidi Clinic, Kampa District. Based on the simulthan test results, the variable of facilities and services rates have a significant effect with together on the patient visits at Junaidi Doctor’s Clinic Kampa District. While based on the partial test results, the variable of facilities and services rates have a significant effect with individual on the patient visits at Junaidi Doctor’s Clinic Kampa District. The closeness of the relationship that occurs between the atractiveness of facilities and services rates on the patient visits at Junaidi Doctor’s Clinic Kampa District is very strong with a correlation coefficient R of 83,9%. While contribution of facilities and services rates variable on the patient visits at Junaidi Doctor’s Clinic Kampa District is equual to 69,8% while the remaining 30,2% is influenced by other variables not examined in this study.